خبرات الإساءة التي يتعرض لها المراهقون ذوو الشخصية الحدية وعلاقتها بالتقييم السلبي للذات لديهم - اميرة ابوطبل; عمرو رفعت; رشا محمد مبروک (Faculty of Education - Port Said University, 2024)
هدفت الدراسة الحالية إلى التعرف على خبرات الإساءة التي يتعرض لها المراهقين ذوي الشخصية الحدية وعلاقتها بالتقييم السلبي للذات لديهم , من خلال درجات خبرات الإساءة التي يتعرض لها المراهقين(ذكور- إناث) ذوي الشخصية الحدية ودرجات التقييم السلبي للذات(التقدير السلبي- نقص الكفاية) , وقد تكونت عينة الدراسة من (250) طالب وطالبة في المرحلة الثانوية في محافظة بورسعيد, واستخدمت الدراسة المنهج الوصفي الارتباطي, وتمثلت أدوات الدراسة في مقياس خبرات الإساءة, ومقياس الشخصية الحدية, ومقياس التقييم السلبي للذات (إعداد الباحثة), وقد أظهرت النتائج وجود علاقة ارتباطية دالة احصائياً بين أبعاد خبرات الإساءة لدى المراهقين (ذكور- إناث) ذوي الشخصية الحدية وأبعاد التقييم السلبي للذات لديهم, وقد أظهرت النتائج وجود علاقة ارتباطية دالة احصائياً بين اضطراب الشخصية الحدية وأبعاد التقييم السلبي للذات لدى المراهقين .The current study aimed to identify the experiences of abuse that adolescents with borderline personality are exposed to and its relationship to negative self-evaluation, through the degrees of abuse experiences that adolescents (males-females) with borderline personality are exposed to and the degrees of negative self-evaluation (negative estimation - lack of adequacy). The sample of the study consisted of (250) male and female students at the secondary level in Port Said Governorate, and the study used the descriptive correlational approach. A statistically significant correlation between the dimensions of abuse experiences among adolescents (males - females) with borderline personality and the dimensions of negative self-evaluation. The results showed that there is a stat istically significant correlation between borderline personality disorder and the dimensions of negative self-evaluation among adolescents.